2017
DOI: 10.1620/tjem.243.329
|View full text |Cite
|
Sign up to set email alerts
|

Lower Incidence of Cervical Intraepithelial Neoplasia among Young Women with Human Papillomavirus Vaccination in Miyagi, Japan

Abstract: The Japanese national immunization programme for Human Papillomavirus (HPV) started in 2010. Vaccination rates increased up to 70% in women in the 1996-1999 birth. However, the proactive recommendation for HPV vaccine was suspended in 2013, following repeated media reports of adverse events. Vaccination rates plumped to less than 1% in women born since 2002. In this study, incidence of abnormal cytology and histology was examined in terms of HPV vaccination among 5,924 women aged 20 to 24 years in the fiscal y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Few epidemiologic studies have evaluated the population effectiveness of HPV vaccination for CIN2+. 2124,28 A large study in Scotland 22 evaluated the effectiveness of the bivalent HPV vaccine and noted a 50% reduction in CIN2 and 55% reduction in CIN3 for girls ages 13–17 years vaccinated with 3 doses compared with no vaccination; these effects attenuated with increasing age. An Australian study evaluated vaccine effectiveness in girls ages 12–17 (mean age 16 years) and noted a statistically significant 28% reduction in CIN2+ for ≥1 vaccine doses, similar in magnitude to our results, with reduced protection for girls vaccinated at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…Few epidemiologic studies have evaluated the population effectiveness of HPV vaccination for CIN2+. 2124,28 A large study in Scotland 22 evaluated the effectiveness of the bivalent HPV vaccine and noted a 50% reduction in CIN2 and 55% reduction in CIN3 for girls ages 13–17 years vaccinated with 3 doses compared with no vaccination; these effects attenuated with increasing age. An Australian study evaluated vaccine effectiveness in girls ages 12–17 (mean age 16 years) and noted a statistically significant 28% reduction in CIN2+ for ≥1 vaccine doses, similar in magnitude to our results, with reduced protection for girls vaccinated at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the efficacy of the vaccine, Ozawa et al has stated that HPV vaccines cause a significant decrease in the incidence of abnormal cytological findings of the cervix compared to females who weren't vaccinated. More significantly, a significant reduction has also been observed within the diagnosis of cervical intraepithelial neoplasia-2 or worse, histologically [10].…”
Section: The Development Of Vaccine and Its Significancementioning
confidence: 96%
“…Moreover, the search was limited to recent studies from 2016 to 2021 on the topic. The relevant articles have been included in this review as per the following: HPV-related diseases and cancers (2 articles [7,8]), viral cytology (2 articles [9,10], current vaccines and their development (3 articles [4, 11, 12]), and vaccine safety concerns and potential side effects (7 articles [13][14][15][16][17][18][19]). (See References).…”
Section: Search Strategymentioning
confidence: 99%
“…In regard to the vaccine's efficacy, it has been demonstrated that HPV vaccination leads to a significant reduction in the incidence of abnormal cervical cytological findings, compared to those who were unvaccinated. And more importantly, a significant reduction has been seen in the histological diagnosis of CIN2 or worse [17,18]. A dynamic decrease has been demonstrated in the year-over-year rate of abnormal screening results in association with the introduction of the HPV vaccine, i.e., for the birth-year-dependent change in cervical cancer risk 19 .…”
Section: Safety and Efficacy Of Hpv Vaccinationmentioning
confidence: 99%